2007
DOI: 10.1095/biolreprod.106.056556
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lipids Containing Long- and Very Long-Chain Polyunsaturated Fatty Acids in Cryptorchid Rat Testes1

Abstract: The aim of the present study was to examine the effects of experimental cryptorchidism on rat testicular phospholipids and neutral lipids that contain long-chain (C(18)-C(22)) and very long-chain (VLC) (C(24)-C(32)) polyunsaturated fatty acids (PUFA). The weight of the cryptorchid testis was nearly half that of the contralateral control at postsurgical Days 7-10 owing to the depletion of germ cells. Concomitantly, the amounts of major glycerophospholipids (GPL) and sphingomyelin (SM) per testis decreased. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 50 publications
4
16
1
Order By: Relevance
“…phagocytosis, intracellular lipid transport, or metabolism, were temporarily disturbed by these exposures. This delay sharply contrasted with the results of experimental cryptorchidism [9]. In this case, the increase in neutral lipids levels occurred at much faster rates and then decreased, all in the time frame of a few days.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…phagocytosis, intracellular lipid transport, or metabolism, were temporarily disturbed by these exposures. This delay sharply contrasted with the results of experimental cryptorchidism [9]. In this case, the increase in neutral lipids levels occurred at much faster rates and then decreased, all in the time frame of a few days.…”
Section: Discussioncontrasting
confidence: 77%
“…Previous work from our laboratory showed that, in vivo , the heat-stressed rat testis undergoes an intense depletion of lipids that are exclusive of germ cell membranes, as shown after experimental cryptorchidism [9] and after experimental hyperthermia [10]. In both models, glycerophospholipids (GPL) rich in long-chain polyunsaturated fatty acids (PUFA) like 20:4n-6 and 22:5n-6, and sphingomyelins (SM) rich in very long chain PUFA (VLCPUFA) like 28:4n-6 and 30:5n-6, disappeared as the last mature germ cells abandoned the testis and seminiferous tubules became almost exclusively populated by SC.…”
Section: Introductionmentioning
confidence: 79%
“…Salmon Elovl4 showed high efficiency in the elongation of C20 and C22 PUFA substrates that led to the production of n-3 and n-6 polyenes containing up to C36. The VLC-PUFA are FA uniquely found in specific lipid molecules of retina (Alvedaño, 1987(Alvedaño, , 1988), brain (Robinson et al, 1990), and testis (Furland et al, 2003(Furland et al, , 2007aZadravec et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated in vitro that lipid β-oxidation is a major pathway for the production of ATP, and that phagocytosis of apoptotic spermatogenic cells increases ATP production and lipid droplet accumulation in the Sertoli cells of mouse testes [36]. In cryptorchid rat testes, which could be considered as hyperthermic, the amount and concentration of triglycerides and cholesterol esters increased several fold [37]. In the current study, we found that transient scrotal hyperthermia induced lipid droplet accumulation in murine testes.…”
Section: Discussionmentioning
confidence: 99%